2015
DOI: 10.2174/1574887110666150317121413
|View full text |Cite
|
Sign up to set email alerts
|

The ModifiedGlasgow Prognostic Score and Survival in Colorectal Cancer: A Pooled Analysis of the Literature

Abstract: A high m-GPS is associated with poor OS in colorectal cancer. The m-GPS is a cheap and easily evaluable biomarker, and its incorporation into known prognostic scores for clinical decision making warrants further investigation in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
1
20
0
3
Order By: Relevance
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The CRP/ALB ratio was calculated from the preoperative blood samples by dividing the serum CRP level by the serum ALB level. The mGPS was defined according to the methods of a previous report (Petrelli et al 2015 ), using the combination of the serum CRP and ALB levels: patients with a CRP level of <1.0 mg/dl were allocated a score of 0; those in whom the CRP and ALB levels were ≥1.0 mg/dl and ≥3.5 g/dl, respectively, were allocated a score of 1; and those in whom the CRP and ALB levels were ≥1.0 mg/dl and ALB < 3.5 g/dl, respectively, were allocated a score of 2. The neutrophil to lymphocyte ratio (NLR) was calculated from a blood sample by dividing the absolute neutrophil count by the absolute lymphocyte count.…”
Section: Methodsmentioning
confidence: 99%
“…CRC-ben 9 vizsgálat (n = 2227) metaanalízise alapján az emelkedett mGPS rövidebb teljes túléléssel társult (HR 1,69 [95%-os CI 1,4-2,04], p<0,00001) [22].…”
Section: Eredményekunclassified